Discovery of giant unit-cell super-structure in the infinite-layer nickelate PrNiO2+x - Jens Oppliger; Julia Küspert; Ann-Christin Dippel; Martin v. Zimmermann; Olof Gutowski; Xiaolin Ren; Xingjiang Zhou; Zhihai Zhu; Ruggero Frison; Qisi Wang; Leonardo Martinelli; Izabela Biało; et al. (Communications Materials)
Abstract The discovery of unconventional superconductivity often triggers significant interest in associated electronic and structural symmetry breaking phenomena. For the infinite-layer nickelates, structural allotropes are investigated intensively. Here, using high-energy grazing-incidence x-ray diffraction, we demonstrate how in-situ temperature annealing of the infinite-layer nickelate PrNiO2+x (x ≈ 0) induces a giant superlattice structure. The annealing effect has a maximum well above room temperature. By covering a large scattering volume, we show a rare period-six in-plane (bi-axial) symmetry and a period-four symmetry in the out-of-plane direction. This giant unit-cell superstructure—likely stemming from ordering of diffusive oxygen—persists over a large temperature range and can be quenched. As such, the stability and controlled annealing process leading to the formation of this superlattice structure provides a pathway for novel nickelate chemistry.